2003
DOI: 10.1177/153537020322800806
|View full text |Cite
|
Sign up to set email alerts
|

Urinary chiro-Inositol and myo-inositol Excretion is Elevated in the Diabetic db/db Mouse and Streptozotocin Diabetic Rat

Abstract: Inositol phosphoglycan molecules containing either D-chiro-inositol or myo-inositol have been isolated from various mammalian tissues and are putative mediators of insulin action. Urinary excretion of inositols appears to be altered in diabetes mellitus; however, the relationships with different types of diabetes are unclear. The objective of this study was to determine the urinary excretion of chiro- and myo-inositol in diabetic animal models, including streptozotocin (STZ) rats, db/db mice, and fa/fa Zucker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 21 publications
3
39
1
4
Order By: Relevance
“…[107] In a rat model of type 1 diabetes and a mouse model of type 2 diabetes the urinary excretion of D-chiro-inositol was much greater than in healthy rats and mice. [108] These studies contradict earlier work showing a lower urinary excretion (and lower muscle content) of D-chiro-inositol in non-insulin-dependent diabetics than in nondiabetics. [109] The transport into cells of D-chiro-inositol by SMIT2 is up-regulated by insulin so the increased urinary excretion of D-chiro-inositol in diabetics may be due to the lack of activity of SMIT2 consequent upon a shortage of insulin.…”
Section: D-chiro-inositol Diabetes Pregnancy and Polycystic Ovary Scontrasting
confidence: 64%
“…[107] In a rat model of type 1 diabetes and a mouse model of type 2 diabetes the urinary excretion of D-chiro-inositol was much greater than in healthy rats and mice. [108] These studies contradict earlier work showing a lower urinary excretion (and lower muscle content) of D-chiro-inositol in non-insulin-dependent diabetics than in nondiabetics. [109] The transport into cells of D-chiro-inositol by SMIT2 is up-regulated by insulin so the increased urinary excretion of D-chiro-inositol in diabetics may be due to the lack of activity of SMIT2 consequent upon a shortage of insulin.…”
Section: D-chiro-inositol Diabetes Pregnancy and Polycystic Ovary Scontrasting
confidence: 64%
“…Due to its role as a second messenger in the signal transduction processes, several clinical trials (10)(11)(12)(13)(14)(15)(16) have suggested a beneficial effect of inositol (myo-or chiro-) supplementation in improving ovarian function, hormone status and glucose homeostasis, with no reported side effects, For this reason, it may potentially be used on a population-wide level.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in myo-inositol and in D-chiro-inositol metabolism have been involved in the development of several diseases and in particular in the development of IR and diabetic complications (11,12).…”
Section: The Influence Of D-chiro-inositol and D-myo-inositol In Pregmentioning
confidence: 99%
“…In diabetes, the depletion of intracellular myo-inositol pools related to increased synthesis of sorbitol from glucose with accentuated AR activity in the renal medulla and increased urinary excretion of MI to maintain homeostasis inside the cell is described in ref. 34. Thus, the increased RSOR͞MIOX activity in the renal cortex in diabetes can be ascribed to the maintenance of homeostasis and osmoregulation in the kidney by catabolizing glucose intermediaries, e.g., myo-inositol.…”
Section: Discussionmentioning
confidence: 99%